CONCENTRATION OF AMINO-ACIDS BY A LIQUID EMULSION MEMBRANE WITH A CATIONIC EXTRACTANT - HONG, SA; CHOI, HJ; NAM, SW (ELSEVIER SCIENCE BV, 1992)
The concentration of L-phenylalanine in a liquid emulsion membrane system was studied using a cation complexing agent, di-2-ethylhexyl phosphoric acid (D2EHPA), as a carrier. The membrane formulation, the pH in the internal phase and the acid concentration in the external phase were optimized with respect to concentration performance and membrane stability. It was found that a liquid emulsion membrane obtained by demulsification of the emulsion by an electrostatic coalescer could be reused. Based on the laboratory tests, a continuous multistage process for the concentration of amino acids was proposed (with the development of a commercial process in mind) and its technical feasibility was discussed.
Keywords: W/O EMULSION; DEMULSIFICATION; SEPARATION